The nature and extent of prisoners' social care needs: Do older prisoners require a different service response?. (May 2021) - Tucker, Sue; Hargreaves, Claire; Cattermull, Mark; Roberts, Amy; Walker, Tammi; Shaw, Jennifer; Challis, David
Summary: In light of longstanding concern about the lack of social care in prisons, the 2014 Care Act made local authorities in England responsible for identifying, assessing and meeting prisoners' social care needs. However, service planning is difficult, for little is known about the level of demand or the extent to which the needs of older and younger prisoners differ. Against this background, face-to-face interviews (including screens for social care needs, substance misuse and mental health problems) were undertaken with a sample of male prisoners in North-West England. Findings: Three hundred and ninety-nine participants were aged 18–49 and 80 aged 50 plus. Overall, more than a 10th of participants had problems maintaining personal hygiene, dressing and/or getting around the prison safely; a significant minority lacked meaningful occupation; and approaching a sixth acknowledged problems forming/maintaining relationships. Older prisoners were significantly more likely than younger prisoners to need help with personal hygiene, dressing and moving around safely and to identify problems with their physical health and memory. Applications: The findings highlight the substantial number of older prisoners who could potentially benefit from some form of social care and support if they are to maintain their safety and dignity and make best use of their time in prison. They also underline the need to develop suitable screening and assessment tools for older prisoners, and for further research on the best service models for prisoners requiring intimate personal care.